IPOs in Nordic countries during the COVID-19 : A Comparative Study of IPOs returns on the Nordic Stock Exchanges - Alapiha, Jukka Johannes (My University, 2025)
The COVID-19 pandemic surprised investors in March 2020 and caused a sharp market drop, with major stock indices falling by over 30%. The pandemic led to a significant increase in IPOs on stock exchanges, and during the hot issue market, IPO underpricing increased. According to previous studies, as IPO volumes increase, underpricing also grows because companies go public when markets are favorable. IPOs of small and growing companies are more uncertain, and in vestors demand more underpricing for the risk they take. In response to the pandemic, central banks introduced stimulus measures and lowered interest rates as monetary policies. With interest rates in the Eurozone already negative during that time, central banks further increased asset purchases. The rapid market recovery, strong capital in flows, and growing digitalization encouraged many companies to take on more risk and go pub lic. High investor confidence, influenced by many factors, led to a surge in IPO activity. Many com panies experienced significant underpricing on their first day of trading as the market heated up. Heated markets attract smaller, younger, and technology-oriented companies, which tend to have higher than average underpricing. We analyze the IPOs in more detail using firm char acteristics and industry distribution to determine whether there was a difference in underpricing between the periods when these factors are taken into account. This study looks at the IPOs of Nordic companies that went public during the COVID-19 years of 2020–2021 and compares them to those before the pandemic, from 2015 to 2019. The research compares underpricing and the effect of firm-level characteristics on underpricing. The research results were statistically insignificant. Individual firm-level characteristics did not significantly affect underpricing between the COVID-19 period and the non-COVID period. A slight significance was observed in the M/B ratio, but it did not reach statistical significance. Therefore, in the Nordic countries, no significant impact on IPO underpricing measured by firm characteristics was observed.
Keywords: COVID-19; listing (stock market); Nordic countries; pandemics; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance